INVESTMENT DIRECTIONS AND PRINCIPLES OF ENTREPRENEURSHIP DEVELOPMENT IN THE REGIONS - Namozov, A.Sh. (THE INNOVATION ECONOMY, 2024)
The article examines the trends in the evolutionary development of small businesses and private entrepreneurship. The directions of theoretical analysis of scientists in the category of entrepreneurship are indicated. The assessment of the conditions created for entrepreneurship and indicators of organizational and economic development are analyzed. The mechanism for ensuring economic and financial balance of entrepreneurship in the regions has been studied. The role of economic entities and their activities in investment policy is also studied. Directions for solving existing problems in the field of entrepreneurship through direct and foreign investment are indicated. The article proposes principles as the basis for investment directions of entrepreneurship.